On pseudo-slant submanifolds of nearly trans-Sasakian manifolds - Srivastava, Vibha; Prasad, Rajendra (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This paper consist the study of pseudo-slant submanifolds of nearly trans-Sasakian manifolds. Integrability conditions of the distributions on these submanifolds are worked out. Some interesting results regarding such manifolds have also been deduced. An example of a pseudo-slant submanifolds of nearly trans-Sasakian manifold is constracted.